Genetic response to selection on reindeer calf weights - Rönnegård, Lars; Danell, Öje (Rangifer, 2003)
Selection response was investigated after 11 years of selection in the herding district of Ruvhten Sijte in Sweden (63°N,12°E) by comparing the weights of calves owned by herders applying selection with the weights of calves owned by herders not applying selection. Three owner groups in Ruvhten Sijte have selected calves at the autumn slaughter every year since 1986 by retaining heavy calves. They own approximately 45% of the reindeer in Ruvhten Sijte. The other owners do not select on recorded weights, and all animals mix during the mating season. The recorded data on calf weights (1986 to 1997) consisted of 12 484 observations, with mean selection differentials of 2.9 kg and 4.6 kg for female and male calves, respectively (phenotypic standard deviation equal to 4.4 kg). The female generation interval was 6.4 years. In 1996 and 1997, autumn live weights of calves owned by herders applying selection (n = 971) were compared with the weights of calves owned by herders not applying selection (n = 1125). The observed difference was 0.67 kg (total mean = 42.6 kg), of which 0.32 kg was due to differences in dam age structure between the two types of herds, therefore the estimated difference in selection response was 0.35 kg. The realized heritability was 0.2. The potential response that would have been realized if the selected part of the herd had been isolated from gene flow was predicted to be 2.0 kg. In conclusion, the introduction of a selection programme applied by all owners in a herding district would result in an increase in calf weights of approximately 2 kg after two generations of selection.